(untitled) (European Journal of Behavioral Sciences, 2023)
Respiratory-type pandemics such as COVID-19/SARS-CoV-2, severe acute respiratory syndrome/SARS-CoV-1, and Influenza Type A, virus/H1N1, are distinguished by the special feature of the contagiousness of the disease that subsequently imposes social isolation measures and school closures. Therefore, the particular circumstances of respiratory-type pandemics give rise to acute needs for psychosocial adaptation and resilience of children and adolescents. The aim of this study is to establish a model of psychosocial and resilience interventions for children and adolescents to prevent and respond to respiratory-type pandemics. The Method focused on observation and correlation of pandemic-themed studies to design a distinct model of prevention for respiratory-type pandemics. The Results of the study highlighted particular needs in individual time periods Pre-Crisis, IN-Crisis and After-Crisis. The IN-Crisis intervention highlights three, individual subcategories of interventions for the period a) pandemic outbreak, b) closure & quarantine and c) opening. The content of the methodological approaches and intervention techniques were derived from a systematic review of relevant interventions.